Observáveis de Matéria Escura como um Férmion de Majorana - Santos, Maíra Dutra Vasconcelos dos (2014)
Dark Matter (DM) is a key piece for our understanding of the universe evolution. Its existence has been confirmed by gravitational effects on the known matter, and we do not know its constitution just yet. The assumption that DM is composed of particles demands an extension of the Standard Model of Elementary Particles (SM). There are many experiments searching for neutral, stable, weakly interacting particles so called WIMPs, but no conclusive positive signal has been observed so far. That being said, we propose a Majorana fermion to be our DM candidate in one of the simplest minimal extensions of the SM, which adds to the scalar sector a neutral scalar that mixes to the Higgs boson. Further, we study another model which supplements the former by adding a charged scalar, which mediates interactions between the DM particle and leptons. In both models, we compute the relic density, the scattering cross section off nucleon (Direct Detection), and its annihilation rate in Standard Model particles (Indirect Detection) using the numerical package micrOMEGAs. In conclusion, we interestingly find that such models have regions of the parameter space yielding the right abundance while compatible with direct and indirect detection limits. Lastly, we investigate the possibility having the Majoron risen in our extensions as dark radiation in the light of the recent CMB spectrum analyses.